IgG4-related disease of duodenal obstruction due to multiple ulcers in a 12-year-old girl - Daiki Kato; Hiroo Uchida; Akinari Hinoki; Wataru Sumida; Chiyoe Shirota; Satoshi Makita; Masamune Okamoto; Aitaro Takimoto; Shunya Takada; Yoichi Nakagawa (BMC, 2023)
Abstract Background Immunoglobulin G4-related disease (IgG4-RD) is a systemic inflammatory disease and affected individuals typically present with an increased infiltration of IgG4-positive plasma cells in the pancreas, hepatobiliary tract, and liver but rarely in the gastrointestinal tract. Case presentation A 12-year-old girl presented with vomiting and poor weight gain. Gastroscopy revealed duodenal stenosis and ulceration. Computed tomography revealed edematous duodenal wall thickening and air-fluid levels on the right side of the duodenum, which suggested duodenal perforation or penetration. She underwent pancreaticoduodenectomy, and IgG4-RD was diagnosed via histopathology. Conclusions This is the first pediatric case of isolated duodenal IgG4-RD resulting in duodenal obstruction after multiple ulcers. Gastrointestinal IgG4-RD should be among the differential diagnoses of unexplained gastrointestinal obstruction or ulceration even in children.